IMPACT OF INTERVENTIONS OF HUMAN RESOURCES ON EMPLOYEE COMPETENCY BASED PERFORMANCE IN PAKISTANI ORGANIZATIONS - Khaskheli, Ghulam Akbar; Veesar, Muhammad Hassan; Mangi, Qamar Abbas; Ali Rajper, Zulfiqar (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to find the interventions of human resources on the employee competency- based performance in the organization. The survey research design was adopted. The sample size for the study was• Judgmental sampling technique was utilized to conduct this study. Data collection was carried out by a questionnaire adapted from studies. The questionnaire consisted of 7 items demography and 28 items based on the five points Likert scale. Altogether, hypotheses were coherent with the studies conducted earlier and the literature review. This section will further elaborate on the findings of the hypothesis and their significance with the literature review. Results of the study are evident that HR Interventions such as Training & Development, Coaching, Delegation & Empowerment, and Workplace Stress have an impact on Employee Performance. As per findings, the first hypothesis to confirm the influence of Training & Development on Employee Performance is significant. The results of the regression indicate that the predictor Training explains 92% of the variance (R2=0.27, p